Competitive Adsorption and Desorption of 2,4-D and PCOC in a Volcanic Soil - Sridhar Susarla; G.V. Bhaskar; S.M. Rao Bhamidimarri (Adsorption Science & Technology, 1991)
The competitive adsorption and desorption of 2,4-D and PCOC, two of the commonly used phenoxy herbicide chemicals, in a volcanic soil has been examined. A Freundlich-type isotherm incorporating competition between the solutes was used to analyze the adsorption and desorption data. The competition coefficients for 2,4-D and PCOC were linearly dependent on the initial concentration for adsorption and on the amount adsorbed for desorption. The adsorption capacities of 2,4-D and PCOC in a bicomponent system were reduced by 10% and 8%, respectively, in comparison to their single-component values. The desorption studies showed that both 2,4-D and PCOC were difficult to desorb in a bicomponent system.